2010
DOI: 10.1097/prs.0b013e3181ef90cb
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Trial on the Use of Antibiotics in Hand Surgery

Abstract: The authors do not support the use of antibiotic prophylaxis for surgery of the hand. Its use should be preserved for specific infections or for patients with certain types of risk factors for infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 42 publications
3
40
1
Order By: Relevance
“…Similar to Aydin and colleagues, 22 our study does not support an effective role for antimicrobial prophylaxis in elective hand surgery with operative times greater than 2 hours. However, owing to the limited number of patients with longer operative times, we can neither recommend nor discourage use of prophylaxis with longer operative periods.…”
Section: Ssi Risk Factorssupporting
confidence: 81%
“…Similar to Aydin and colleagues, 22 our study does not support an effective role for antimicrobial prophylaxis in elective hand surgery with operative times greater than 2 hours. However, owing to the limited number of patients with longer operative times, we can neither recommend nor discourage use of prophylaxis with longer operative periods.…”
Section: Ssi Risk Factorssupporting
confidence: 81%
“…Six Infected wound (class IV), typical of those excluded from this analysis. This appearance is suggestive of tenosynovitis, usually treated with urgent surgical washout, antibiotics and elevation studies 14,15,17,19,20,26 gave a cephalosporin, four 16,18,22,25 penicillin (flucloxacillin or co-amoxiclav) and three 21,23,24 included any antibiotic prescribed. The trials were statistically homogeneous (P = 0⋅77, χ 2 test, I 2 = 0 per cent), but a random-effects model was used owing to the heterogeneity of regimens.…”
Section: Resultsmentioning
confidence: 98%
“…Among the RCTs, the risk of bias was low in two relatively recent trials 17,25 , high in two trials 15,16 , and one older trial 26 did not describe its study design in sufficient detail to assess some forms of bias. All five prospective trials were at high risk of bias in at least one area, mostly owing to lack of blinding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized controlled trial of preoperative antibiotics versus placebo in 1,340 hand surgery patients, the incidence of surgical-site infection was 3.2% (AE 0.6%). 22 The majority of these patients underwent emergent procedures. The authors found no significant difference in infection incidence between antibiotics and placebo.…”
Section: Discussionmentioning
confidence: 99%